Factors Influencing Malaysian Users’ Satisfaction and Loyalty of Mobile Instant Messaging (MIM) Apps Services - Lu, Wenwen (2013)
As wireless technology develops, more and more people are becoming familiar with Mobile Instant Messaging (MIM) as a means of communication due to its convenience for consumers. It is most widely adopted by young adults. As more people start using this mode of messaging there is an increase in the MIM providers’ competition. In the face of competition, MIM service providers want to attract more users and increase their market share. However, in order to do this, providers need to build a good relationship with consumers which can develop consumer loyalty, which is the key factor to gain the market share. This study aims to investigate the factors influencing Malaysian user’s satisfaction and loyalty of Mobile Instant Messaging (MIM) Apps services. The significance of this study is to better understand users’ needs and to allow opportunity for MIM provides to create better apps in view of offering better services to customers. This research uses the descriptive research design and a primary method of data collection. In addition, SPSS 20 and PLS are used to analyze the data. SPSS was used to analyze the descriptive demographic and PLS was used to test the relationship of the constructs.